PERLINDUNGAN KEKAYAAN INTELEKTUAL ATAS SISTEM ALGORITMA REKOMENDASI PADA PLATFORM DIGITAL: KAJIAN HUKUM DAN ETIKA TELEMATIKA - Neyla Rida Shakira (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The rapid advancement of digital technology has positioned recommendation algorithm-based platforms as strategic components in determining how information is accessed, distributed, and consumed within cyberspace. These algorithms are developed through sophisticated data processing and computational modeling techniques that possess substantial economic value, thereby raising legal debates regarding their status as objects of Intellectual Property Rights (IPR). This study aims to examine the forms of intellectual property protection applicable to recommendation algorithm systems used by digital platforms and to analyze the implications of their implementation from the perspective of telematics ethics. The research employs a normative juridical approach through the examination of statutory regulations, legal doctrines, and practices developing within the digital industry. The findings reveal that recommendation algorithms may qualify for legal protection as trade secrets or patents, provided they fulfill the requirements of confidentiality, economic value, and identifiable technical features. Nevertheless, the implementation of such protection continues to face significant challenges, particularly due to the absence of comprehensive regulations governing algorithmic transparency, personal data protection, and the potential for digital discrimination resulting from algorithmic modeling processes. The study concludes that strengthening intellectual property protection for recommendation algorithms should be accompanied by the application of telematics ethics principles, including accountability, proportional transparency, and respect for users' rights, in order to ensure that technological innovation remains aligned with the public interest and the principles of digital justice.